Elderly physical wellbeing system - Ching, Yu Xuan (Nanyang Technological University, 2021)
With the increasing ageing population in Singapore, there is bound to be an increase in the number of health issues. Along with the increase in number of health issues, there will be an increase in demand for healthcare. One treatment method of taking care of elderlies with health issues is building nursing homes. However, the number of nursing home staffs are not sufficient to handle the increasing number of elderlies. Furthermore, there is a lack of required attention from the staffs to monitor the elderlies doing physiotherapy exercises, in a nursing home. With the improvement of technology around the world, it is observed that almost one-third of the world’s population owns a smart device, and the number of elderlies owning a smart device is constantly on an increase. As most elderlies own a smart phone, one solution for the lack of monitoring of elderlies doing physiotherapy exercise in a nursing home can be proposed, which is to implement a system whereby elderlies are able to carry out physiotherapy exercises without the staffs’ monitoring. The Elderly Physical Well Being System is a system specially designed to resolve the issue that is brought by the increasing demand for physiotherapy treatment. It allows the elderlies to carry out physiotherapy exercises on their own, while motivating them to keep fit. The system consists of two main components. The first component consists of an Arduino Low-Energy Bluetooth board, and an attached orientation sensor device which retrieves, processes, and sends back useful data for exercise implementation. The second component is an Android smart device, which is mainly used as an interface displayed to the user, to perform the exercises and viewing their exercise scores accordingly.